Strategi Tata Kelola Komunikasi Balai Pelestarian Cagar Budaya Provinsi Sulawesi Selatan Dalam Peningkatan Kunjungan Wisatawan Benteng Fort Rotterdam Makassar - Hidaya A , Nurul; Majid , Abd; Rabiah , Sitti (UNIVERSITAS MUSLIM INDONESIA, 2022)
The purpose of this study is to find out how the Communication Governance Strategy of the Cultural Heritage Preservation Center in Increasing Tourist Visits Fort Rotterdam Makassar Fort and how the Communication Governance Process of the Preservation Conservation Center in Increasing Tourist Visits Fort Rotterdam Makassar Fort. This research lasted for 1 month and is located in Makassar City, precisely at the Office of the Cultural Conservation Preservation Center of South Sulawesi Province. The informants in this study amounted to six people. The research method used is qualitative research methods. Descriptive analysis with data collection techniques is carried out in two ways, believe primary data and secondary data. The method of collecting data is by conducting observations, interviews, and documentation. The results of the study, it can be concluded that the Communication Management Strategy carried out by the Cultural Heritage Preservation Center has created excellent and quality information services through its way of implementing communication governance strategies to increase tourist visits. However, this strategy is not very successful in increasing tourist visits every year. It is possible that we have difficulty implementing it so that we fail to achieve the goal. To achieve the goal, of course will get some obstacles.